Pneumococcal Colonization and the Nasopharyngeal Microbiota of Children in Botswana. (4th October 2017) - Kelly, Matthew; Surette, Michael; Smieja, Marek; Rossi, Laura; Luinstra, Kathy; Steenhoff, Andrew; Goldfarb, David; Arscott-Mills, Tonya; Boiditswe, Sefelani; Rulaganyang, Ikanyeng; Muthoga, Charles; Lechiile, Kwana; et al.
Abstract: Background: Streptococcus pneumoniae is the predominant bacterial respiratory pathogen during childhood. Nasopharyngeal colonization precedes infections caused by S. pneumoniae . Interactions between S. pneumoniae and the nasopharyngeal microbial communities of children are poorly described. Methods: We collected nasopharyngeal swabs from 170 children 1 to 23 months of age without pneumonia in Botswana between August 2012 and June 2016. We tested these samples for common respiratory viruses and S. pneumoniae using PCR. We sequenced the V3 region of the bacterial 16S ribosomal RNA gene and used zero-inflated Gaussian distribution mixture models to compare the relative abundances of bacterial genera in children with and without S. pneumoniae colonization. Results: Mean age was 8.3 months, and 51% were female. Ninety-six (56%) children were colonized with S. pneumoniae and 59 (35%) had one or more respiratory viruses. S. pneumoniae colonization was associated with older age ( P = 0.0001). Upper respiratory symptoms were more frequent in children with S. pneumoniae colonization (60% vs. 32%; P = 0.001), even among children without respiratory viruses (50% vs. 20%; P = 0.002). Principal component analysis using Bray-Curtis distances demonstrated that nasopharyngeal samples clustered by S. pneumoniae detection (Figure 1). S. pneumoniae colonization was associated with higher relative abundances of Haemophilus, Moraxella, and Streptococcus, and lower relative abundances of Corynebacterium and Staphylococcus (Figure 2). Respiratory virus infection had no appreciable effect on the composition of the nasopharyngeal microbiota. Conclusion: S. pneumoniae colonization is associated with substantial alterations of the nasopharyngeal microbiota of children independent of respiratory virus co-infection. Prospective studies are needed to determine the extent to which the nasopharyngeal microbiota modifies S. pneumoniae colonization risk. Disclosures: All authors: No reported disclosures.